2006
DOI: 10.1097/01.sla.0000193806.81428.6f
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Surgery May Be Associated With Severe Pain and High Analgesia Requirements in the Immediate Postoperative Period

Abstract: Among patients after abdominal surgery with severe immediate (0-4 hours) postoperative pain, laparoscopic patients are a significant (46%) proportion, and their pain is more intense, requiring more analgesics than painful patients (54%) do after laparotomy. By 24 hours, the former are in less pain than the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 16 publications
2
81
1
4
Order By: Relevance
“…An increase in sympathetic tone may occur due to the sustained pressure from the pneumo-peritoneum on retroperitoneal and para-aortal nerve tissue, splanchnic bed, abdominal and retroperitoneal viscera [10]. Similarly, the CO 2 absorbed from the peritoneal cavity may cause sympathico-excitation [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in sympathetic tone may occur due to the sustained pressure from the pneumo-peritoneum on retroperitoneal and para-aortal nerve tissue, splanchnic bed, abdominal and retroperitoneal viscera [10]. Similarly, the CO 2 absorbed from the peritoneal cavity may cause sympathico-excitation [12].…”
Section: Discussionmentioning
confidence: 99%
“…We choose to compare LPS and LPT abdominal surgeries for the reason that there are data that show the presence of differential stressful stimuli between the two procedures [10,11]. For example, during the first postoperative hours laparoscopic surgery is associated with more severe pain and increased analgesic requirements compared to patients after a laparotomy [10]; and during surgery LPS abdominal surgery is associated with enhanced metabolic and stress hormonal responses compared to open surgery [11]. In the current study we use the pulse transit time as a marker of sympathetic tone and a possible surrogate marker of the nociceptive state of the patient and consequently expect significant differences in PTT values between the two surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain after surgery has been reported to be a consistent problem, which has spanned several decades (Marks & Sachar 1973, Seers 1987, Svensson et al 2000, Wu et al 2002. Nearly half (n = 67) of 145 patients admitted to a postanaesthesia care unit experienced severe pain within a 30-min postoperative period (Ekstein et al 2006). The reasons for this are well documented and include patient barriers, inadequate knowledge of health care professionals, lack of assessment and organisational practices which frequently impede the administration of analgesics and non-pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, a recent study observed that laparoscopic surgery is associated with higher pain scores in the first hours postoperatively [16]. Others described higher nociceptive pain scores during laparoscopic procedures compared to conventional open surgery [17].…”
Section: Introductionmentioning
confidence: 98%